2011
DOI: 10.1186/1756-3305-4-66
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in Trypanosoma cruzi: the role of Serratia marcescens prodigiosin in the alternative treatment of Chagas disease

Abstract: BackgroundChagas disease is a health threat for many people, mostly those living in Latin America. One of the most important problems in treatment is the limitation of existing drugs. Prodigiosin, produced by Serratia marcescens (Rhodnius prolixus endosymbiont), belongs to the red-pigmented bacterial prodiginine family, which displays numerous biological activities, including antibacterial, antifungal, antiprotozoal, antimalarial, immunosuppressive, and anticancer properties. Here we describe its effects on Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 49 publications
(54 reference statements)
1
30
1
1
Order By: Relevance
“…the pig operon), the notorious red pigment, which is widely-conserved across several Serratia isolates [ 38 ]. Prodigiosin is most commonly found in environmental S. marcescens isolates and has been proposed to suppress growth of various fungi [ 47 ], bacteria [ 97 ], protozoans [ 98 ] and even viruses [ 99 ]. It has been recently suggested that prodigiosin has affinity for the lipid bilayer of the plasma membrane, causing outer membrane damage [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…the pig operon), the notorious red pigment, which is widely-conserved across several Serratia isolates [ 38 ]. Prodigiosin is most commonly found in environmental S. marcescens isolates and has been proposed to suppress growth of various fungi [ 47 ], bacteria [ 97 ], protozoans [ 98 ] and even viruses [ 99 ]. It has been recently suggested that prodigiosin has affinity for the lipid bilayer of the plasma membrane, causing outer membrane damage [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…The facultative anaerobe S. marcescens biotype A1 isolated from the gut of R. prolixus has been reported to have trypanolitic activity, especially on the Y strain [ 85 ]. Prodigiosin, a pigment in some strains of these bacteria, has been proposed to be responsible for trypanocidal activity [ 85 , 86 ]. However, Castro et al [ 87 , 88 ] proposed that mannose sensitive fimbriae might be directly involved in the trypanocidal activity by connecting bacteria to the surface of the parasite and promoting their adhesion to the protozoan cellular membrane.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting example is the study about the control of Chagas disease, which severely affects the health of the human population in Latin America and which is caused by the protozoan parasite Trypanosoma cruzi. Genes et al (2011) reported such bacteria species as Serratia marcescens biotype A1a, which is regularly found in the gut of the vector insect Rhodnius prolixus, and which demonstrates the trypanolytic activity conferred by prodigiosin. Prodigiosin is a potent bacterial tripyrrolic compound with various biological activities.…”
Section: The Highly Conserved Mitochondrial Machinery Of Invertebratementioning
confidence: 99%